Supplements use in elite athletes in relation to attitudes, beliefs and knowledge - Morente-Sanchez, J.; Zabala, M. (Medicina Sportiva, 2014)
Introduction: Doping in sports has been studied from different perspectives such as medical, physiological and social science; however, being a taboo topic, it is not easy to get objective information on use of banned performance enhancing substances. There is a continuous focus for years on determination of predictors of doping behaviour. In order to obtain a reliable view of how widespread is the doping in sports, determining the prevalence of doping is a prime goal for many international and national sport-governing bodies. Objective: To gather and critically examine the most recent publications describing elite athletes` prevalence rates of supplements and banned substances. Methods: A systematic literature search was performed using a set of relevant criteria and a set of doping-related keywords to identify potentially relevant articles. We searched PubMed, Medline, Web of Knowledge, Scopus, and SPORTDiscus using a set of doping-related keywords to identify potentially relevant articles. We next performed a manual search of the references cited in the studies retrieved in the electronic search. Results: A total of 22 papers, which reported the prevalence rates of doping and supplements use in elite athletes from different sports, were retrieved and evaluated. Conclusion: As expected, the frequencies of non-banned substances use are higher than doping substances. However, the use of supplements is widespread existing among different sports and countries, so this should be analysed exhaustively to intervene more effectively on those potentially risky users from prevention perspective.